Quantitative Descriptive Study on the Contribution of Oil Palm Farming Income to Farmers’ Household Expenditures - Sri Handayani; Aswin Nasution; Ramayana; Sufriadi; Qhistina Atikah; Bagio; Yusmaniar (Jurnal Penelitian Pendidikan IPA, 2025)
Indonesia is the world’s largest producer of palm oil, a strategic commodity that significantly underpins the national economy and serves as the main source of income for millions of smallholder farmers. While oil palm cultivation is often associated with high and relatively stable financial returns, providing a vital pathway out of poverty, the actual financial dependence of farming households on this single source of income remains a critical subject of inquiry. This study aims to analyze the, contribution of oil palm farming to fulfilling household needs of farmers in Pante Ceureumen Sub-district, West Aceh Regency. The research employed a purposive sampling method with 100 oil palm farmer respondents. Data were analyzed by calculating the ratio between farming income and total household expenditures. The results indicated that the average income from oil palm farming was IDR 74.003.15 per year, while the average household expenditure was IDR 52.269.00 per year. The contribution of oil palm farming to farmers' household expenditures reached 142 %, signifying that the income derived from oil palms not only covered all household necessities but also yielded a surplus of 42%. This finding demonstrates that oil palm farming plays a vital role in enhancing the welfare of farmer households in the study area.